Arterial Hypertension in Pregnant Woman - Cunha, Vitória (2022)
Hypertensive disorders of pregnancy continue to be acause of maternal and fetal morbidity and mortality, not onlyin pregnancy and peripartum but also in the future life ofthe mother and baby. It is essential not only to understandthe underlying pathophysiological mechanisms, but also toknow how to make the diagnosis with the appropriate methodology, assess the woman’s risk, and know the particular therapeutic options. Surveillance takes into accountthe various types of hypertensive disorders, as the risk ofprogression to potentially serious and/or fatal conditionscan have catastrophic consequences. This article seeks toreview arterial hypertension in pregnant woman in all fundamental aspects, for the most appropriate approach from theinternist’s point of view.